(untitled) (Research, Society and Development, 2024)
Pavlovian and operant conditioning are forms of associative learning in which humans and other animals learn to associate events or stimuli that occur in sequence or together. Skinner coined the term "operant conditioning" to describe how behavior is shaped by its consequences. Recent advances in neuroscience can provide insights into behavior that were unthinkable in Skinner’s time. This study aimed to show a narrative review of the literature on recent advances in understanding the neural bases involved in Pavlovian conditioning and operant conditioning. A literature review was conducted on the neurobiology of Pavlovian and operant conditioning. Studies in invertebrates have highlighted similarities with the forms of learning described in vertebrates by Pavlov, Thorndike, and Skinner. Experiments in simpler nervous systems show that it is possible to advance understanding at the level of neural circuits and molecular mechanisms of psychological concepts inferred from purely behavioral studies.